EXPLORING JAVANESE CHILDRENS’ PLAY SONGS: AN ECOLINGUISTIC PERSPECTIVE - Intan Kharisma Putri, Celya; Prassetyo, Sidarta (Linguistik : Jurnal Bahasa dan Sastra, 2025)
Traditional songs have long served as a medium for cultural transmission, carrying moral lessons and ecological wisdom across generations. In Javanese society, children’s play songs such as Lir-ilir and Gundhul-gundhul Pacul are not merely entertainment but repositories of cultural values that reflect the community’s worldview. However, in an era where globalized media and technology dominate children’s learning environments, the ecological and moral messages embedded in these traditional songs risk being overlooked. This study aims to explore the ecological and cultural values conveyed in these two Javanese children’s play songs through an ecolinguistic discourse analysis approach mainly using Stibbe’s (2015, 2021). The analysis reveals that Lir-ilir highlights themes of renewal, growth, and environmental harmony, while Gundhul-gundhul Pacul emphasizes humility, responsibility, and respect for social and natural balance. These findings suggest that Javanese children’s songs encapsulate ecological wisdom rooted in local culture, which remains highly relevant to today’s environmental challenges. The study highlights the potential of traditional songs as pedagogical and ecolinguistic resources to foster environmental awareness and cultural identity among younger generations.